Progress as Something More than Change - Havlíček, Aleš (Dějiny – teorie – kritika, 2009)
The author is concerned with the introductory chapter of Bedřich Loewenstein’s Víra v Pokrok (Faith in Progress), which is about the assumptions of the idea of progress in Classical Antiquity. As opposed to Loewenstein’s main emphasis on cyclical time and the generally sceptical Classical view of the rise of civilization, he presents several themes that expand the perspective of progress in Classical Antiquity and problematize it. He distinguishes between scientific progress with regard to a previously established aim (particularly in mathematics and the natural sciences) and spiritual progress, which with new knowledge opens previously unknown areas. The dividing line is the Sophist movement and also the Platonic idea of the Good as the horizon of the assumed and as a previously established destination, which must have quality.